2021
DOI: 10.52711/0974-360x.2021.00554
|View full text |Cite
|
Sign up to set email alerts
|

Q-Absorbance Ratio Spectrophotometric Method for the Simultaneous Estimation of Metformin Hydrochloride and Voglibose in Tablet Dosage form

Abstract: A new, simple, accurate, precise and reproducible UV-Spectrophotometric method is being developed for the simultaneous estimation of Metformin Hydrochloride and Voglibose in tablet dosage form. The stock solutions were prepared in methanol. The λmax for Metformin Hydrochloride and Voglibose were found to be248 nm and 287nm respectively. The Metformin Hydrochloride and Voglibose obeyed Beer’s law in concentration range of 8-16µg/ml and 4-20µg/ml respectively. Results of analysis of absorbance ratio method were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…13 Where Cx and Cy are the x and y concentrations, A is the sample's absorbance at iso-absorptive λmax, and a1 and a2 are the x and y absorptivity at iso-absorptive λmax, respectively. QM= A2 / A1 ………………………………..14 QX= a 𝑥 2/ a 𝑥 1 ………..……………………..15 Q y= ay2/ay1 …………………………………16 Where, A1 and A2 were absorbance of combination at λiso and λ max a𝑥 1 and ay1 are absorptivities of 𝑥 and y at λ iso a𝑥 2 and ay2 are absorptivities of 𝑥 and y at λ max [26][27][28]…”
Section: Q-absorbance Ratio Spectra Methodsmentioning
confidence: 99%
“…13 Where Cx and Cy are the x and y concentrations, A is the sample's absorbance at iso-absorptive λmax, and a1 and a2 are the x and y absorptivity at iso-absorptive λmax, respectively. QM= A2 / A1 ………………………………..14 QX= a 𝑥 2/ a 𝑥 1 ………..……………………..15 Q y= ay2/ay1 …………………………………16 Where, A1 and A2 were absorbance of combination at λiso and λ max a𝑥 1 and ay1 are absorptivities of 𝑥 and y at λ iso a𝑥 2 and ay2 are absorptivities of 𝑥 and y at λ max [26][27][28]…”
Section: Q-absorbance Ratio Spectra Methodsmentioning
confidence: 99%
“…Therefore, there is a need to develop a technique to simultaneously measure metformin hydrochloride and repaglinide in bulk and combined tablet dosage forms. An RP-HPLC method was developed for the simultaneous determination of metformin and repaglinide in bulk and composite tablet dosage forms [7][8][9][10][11][12][13][14][15]. The structures of metformin HCl and repaglinide are showed in Figures 1 and 2 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the available literature found that a number of analytical techniques, such as spectrophotometric [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], colorimetric [ 31 , 32 , 33 ], spectrofluorometric [ 33 , 34 , 35 ], and high-performance liquid chromatographic [ 36 , 37 , 38 , 39 ] methods, were described for the detection of linagliptin. It has been determined that colorimetric is more specific than spectrophotometry (UV region).…”
Section: Introductionmentioning
confidence: 99%
“…It has been determined that colorimetric is more specific than spectrophotometry (UV region). The methods used to analyse the LGN singly or in combination are cited in references [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], which were based on the molecular absorption technique. These methods are sensitive, but they are not as selective as the method being studied.…”
Section: Introductionmentioning
confidence: 99%